As Drogas e as Psicoses: sobre a constituição do delírio e as toxicomanias - Ramos, Carlos Eduardo de A. S. (Revista Vernáculo, 2002)
As Drogas e as Psicoses: sobre a constituição do delírio e as toxicomanias